Implementation of Organic and Inorganic Waste Sorting System as an Effort to Improve Environmental Cleanliness - Ramadika Purnama; Abdullathif Assidiq; Vina Gustavia; Rubihatul Husni Ulwani; Ana Mulyasari; Devi Arisanti; Juliana Re Fauzie; Moh Faturrahman; Tarjono Tarjono; Supendi Supendi (Siber Nusantara Research, 2026)
The problem of household waste is still a major challenge in maintaining environmental cleanliness, especially in densely populated areas. Low public awareness in sorting organic and inorganic waste leads to an increase in the volume of mixed waste and a decrease in environmental quality. Community Service (PKM) activities in Sindangsari Village are carried out through the Participatory Action Research (PAR) method, including problem identification, socialization, education, implementation of the waste sorting system, and evaluation. The results of the activity show an increase in public understanding of waste classification and the importance of environment-based management. This program has succeeded in changing people's behavior to sort waste before it is disposed of, reduce the volume of mixed waste, and encourage the use of organic waste into compost and inorganic waste to be recycled or distributed to waste banks. The implementation of this system has proven to be effective in increasing environmental cleanliness and public awareness of sustainable waste management.